Work life after failure? : how employees bounce back, learn, and recover from work-related setbacks - Todt, Gisa; Backmann, Julia; Weiss, Matthias (Emerald Publishing Limited, 2021)
Work environments are paved with challenges and uncertainties that can result in the risk of setbacks and personal failure. Experiencing negative events such as these can be devastating for employees. This results in employees becoming distracted, detaching themselves from work and being unable to effectively engage in their work activities. Work Life after Failure?: How Employees Bounce Back, Learn, and Recover from Work-Related Setbacks brings together the knowledge from three distinct concepts that currently lack integration: resilience, learning, and recovery. The authors regard resilience as the positive adaptation after adversity and examine aspects of learning from failure as a process of improvement through enhanced knowledge and understanding after negative professional experiences. The exploration of recovery is situated in the context of a process of reducing strain symptoms that were caused by work-related events. Together, these three concepts advance our understanding of how to effectively use personal resources to overcome the experience of failure and what organizations can do to support employees during these difficult times. Encompassing both conceptual and empirical work from experts in the fields of resilience, learning from failure, and recovery, this book also sheds light on the classification of failures and setbacks and develops a measure of the setback severity.